Penyisihan Parameter TSS dan COD Menggunakan Koagulan Nanokitin dan Kitosan pada Pengolahan Air Sungai Cikapundung - Memey Suhaya Putri; Etih Hartati; Djaenudin Djaenudin (Fakultas Teknik, 2020)
The use of excessive synthetic coagulants and continuously will have a negative impact because of the increasing amount of mud volume can accumulate in the human body. The quality of Cikapundung River water has decreased every year, so it is necessary to treat Cikapundung River water through a process of coagulation and flocculation using coagulants made from nanocytin, chitosan and commercial chitosan. Measurement of these parameters uses the gravimetric and titrimetri method. The dose of coagulant used in the process of coagulation and flocculation is 10 mg / L, by varying the pH value of pH 5, pH 7 and pH 9 and the flocculation time variations of 15 minutes, 20 minutes and 25 minutes. The measurement results showed with a dose of coagulant 10 mg / L, commercial chitosan pH 5 flocculation times of 25 minutes can reduce the TSS concentration of 12 mg / L with 99.38% total suspended allowance. Concentration of Chemical Oxygen Demand 13.12 mg / L with 98.91% allowance. The TSS value has fulfilled the quality standard according to Government Regulation Number 82 of 2001 concerning Management of Water Quality and Water Pollution Control in the first class.